The Direct Referral to Endovascular Center criteria: a proposal for pre‐hospital evaluation of acute stroke in the Madrid Stroke Network. (19th January 2017) - Rodríguez‐Pardo, J.; Fuentes, B.; Alonso de Leciñana, M.; Ximénez‐Carrillo, Á.; Zapata‐Wainberg, G.; Álvarez‐Fraga, J.; Barriga, F. J.; Castillo, L.; Carneado‐Ruiz, J.; Díaz‐Guzman, J.; Egido‐Herrero, J.; de Felipe, A.; et al.
Abstract : Background and purpose: For patients with acute ischaemic stroke due to large‐vessel occlusion, it has recently been shown that mechanical thrombectomy (MT) with stent retrievers is better than medical treatment alone. However, few hospitals can provide MT 24 h/day 365 days/year, and it remains unclear whether selected patients with acute stroke should be directly transferred to the nearest MT‐providing hospital to prevent treatment delays. Clinical scales such as Rapid Arterial Occlusion Evaluation (RACE) have been developed to predict large‐vessel occlusion at a pre‐hospital level, but their predictive value for MT is low. We propose new criteria to identify patients eligible for MT, with higher accuracy. Methods: The Direct Referral to Endovascular Center criteria were defined based on a retrospective cohort of 317 patients admitted to a stroke center. The association of age, sex, RACE scale score and blood pressure with the likelihood of receiving MT were analyzed. Cut‐off points with the highest association were thereafter evaluated in a prospective cohort of 153 patients from nine stroke units comprising the Madrid Stroke Network. Results: Patients with a RACE scale score ≥ 5, systolic blood pressure <190 mmHg and age <81 years showed a significantly higher probability of undergoing MT (odds ratio, 33.38; 95% confidence interval, 12–92.9). This outcome was confirmed in the prospective cohort, with 68% sensitivity, 84% specificity, 42% positive and 94% negative predictive values for MT, ruling out 83% of hemorrhagic strokes. Conclusions: The Direct Referral to Endovascular Center criteria could be useful for identifying patients suitable for MT.